Tailoring Biodegradability of Poly(Butylene Succinate)/Poly(Lactic Acid) Blends With a Deep Eutectic Solvent - Delamarche, Emma; Mattlet, Agnès; Livi, Sébastien; Gérard, Jean-François; Bayard, Rémy; Massardier, Valérie (Frontiers in Materials, 2020)
Biodegradable polymers concern an important topic for innovation in materials as they are supposed to contribute to the reduction of the amount of waste materials which lead to microplastics with similar properties as conventional polymer materials. Poly(butylene succinate) and poly(lactic acid) blends are polymers with interesting properties offering possible alternatives to some conventional petrochemicals-sourced polymers. Some of the physical properties of such blends can be tailored from the addition of small amounts of deep eutectic solvents which can act as compatibilizers, i.e. interfacial agents between PBS and PLA. In our study, materials formulated with a deep eutectic solvent (DES) having a coarse morphology according to the dispersed particles sizes display thermal and mechanical properties close to the non-compatibilized PBS/PLA blends but a higher ability to biodegrade. Biodegradation experiments showed that PBS/PLA/DES exhibits higher weight losses and faster fragmentation under conventional conditions. A significant decrease of PLA melting temperature under composting conditions, i.e. at 58°C, is observed indicating that PLA phase is the component mainly concerned. As a conclusion, this work demonstrates that morphologies as well as the biodegradability process can be tailored by adding a small amount of a deep eutectic solvent in such biosourced polymer blends. Indeed, designing polymer materials, for which degradation processes are targeted in the dispersed phase, i.e. in multiple locations of the material, could be an efficient route to “predegraded” phases in a polymer matrix in order to accelerate macroscopic biodegradation.